Mapping environmental fragility and maintenance of ecosystem services in an Atlantic Forest region in Pontal do Paranapanema – SP. - Genaro , Vinicius; Pinese, José Paulo Peccinini; Aledo, Antonio (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Ecosystem services (ES) are vital to the well-being and survival of humanity, encompassing a variety of benefits provided by nature, such as soil formation, erosion control, climate regulation, carbon storage, nutrient cycling, water provision, rainfall cycle maintenance, biodiversity protection, and more. Teodoro Sampaio, located between the Paraná and Paranapanema rivers, is home to an extensive stretch of Atlantic Forest, serving as a refuge for endangered species. The region, however, faces significant environmental challenges due to economic activities such as hydroelectric dams, extensive farming, and the growth of foreign-influenced agribusiness. The study sought to assess the environmental fragility of these SE-producing areas, combining potential fragility with land use. Factors such as geomorphology, climate, pedology, and land use were considered. Each variable received a frailty rating (weak, medium, or strong), and these data were combined in the QGIS software with equal weight to produce a map of environmental fragility. This map identified levels ranging from Very Weak to Very Strong in terms of linear erosion and, consequently, in the ability of ecosystems to provide essential services for the region’s development.